The mysterious extravillous trophoblast (2022)
Extravilluos Trophoblast (EVT) is a truly special cell. It has a temporary character and tumor-like behavior and tumor-like appearance, all of which seem to belong to the malignancy fi eld [1,2]. It is also known as intermediate trophoblast, derived from cytotrophoblast [3-5], having formed between the latter and the syncytiotrophoblast. EVT is capable of reaching the decidua through trophoblast cell columns that connect the anchoring villi to the basal plate in early gestation.